2009
DOI: 10.1142/s0192415x09007533
|View full text |Cite
|
Sign up to set email alerts
|

Rhizomes of Gastrodia elata BL Possess Antidepressant-Like Effect via Monoamine Modulation in Subchronic Animal Model

Abstract: Depression is one of the most common psychiatric disorders that affects over 10% of individuals. However there is no desirable therapeutic approach nowadays. Thus, looking for an alternative treatment is important. The objectives of this study are to investigate the antidepressant effects of the rhizomes of Gastradia elata B(L), a traditional Chinese medicine, in the animal model forced-swimming test (FST), and to analyze the monoamine content in the rats' brain regions in order to better understand the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The dry tuber of Tianma has long been officially listed in the Chinese Pharmacopoeia and is used in treating headaches, dizziness, tetanus, epilepsy, infantile convulsions, numbness of the limbs and also for the improvement of cognitive functions (4,(31)(32)(33)(34)(35)(36). From scientific investigations, Tianma possesses anti-oxidative and free radical scavenging (37), neuroprotective (38), and antidepressant effects (7,39,40). Tianma, huperzia serrata and other herbs have recently also been discussed as a relevant source of potential therapeutic remedies that target AD symptoms or the primary pathogenic processes of AD especially as researchers are now exploring the possibility of a connection between AD, VD, diabetes mellitus (type 2, DMT2), and CD (5,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The dry tuber of Tianma has long been officially listed in the Chinese Pharmacopoeia and is used in treating headaches, dizziness, tetanus, epilepsy, infantile convulsions, numbness of the limbs and also for the improvement of cognitive functions (4,(31)(32)(33)(34)(35)(36). From scientific investigations, Tianma possesses anti-oxidative and free radical scavenging (37), neuroprotective (38), and antidepressant effects (7,39,40). Tianma, huperzia serrata and other herbs have recently also been discussed as a relevant source of potential therapeutic remedies that target AD symptoms or the primary pathogenic processes of AD especially as researchers are now exploring the possibility of a connection between AD, VD, diabetes mellitus (type 2, DMT2), and CD (5,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the concentrations of serotonin and dopamine were elevated, while the turnover of these two monoamines was decreased after orally GE treatment 71) . Furthermore, the water extract of GE attenuated memory impairment loss by the animals as measured by the inhibitory avoidance task and the Morris water maze in rats 73) .…”
Section: Discussionmentioning
confidence: 83%
“…In both the forced-swimming test and tail-suspension test, animal models used for evaluation of antidepressant activity, the water and the ethanol extract of GE demonstrated a significant antidepressant effect [70][71][72] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that GE significantly decreased immobility duration in a forced-swimming test in rats, primarily by modulating the serotonergic system (1).…”
mentioning
confidence: 99%